2012
DOI: 10.1177/1470320311435534
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanism of the cardio-renal protective effects of AVE-0991, a non-peptide Mas-receptor agonist, in diabetic rats

Abstract: Hypothesis: This study was designed to investigate the cardio-renal protective effect of AVE-0991, a non-peptide Masreceptor agonist, and A-779, a Mas-receptor antagonist, in diabetic rats. Materials and methods: Wistar rats treated with streptozotocin (50 mg/kg, i.p., once), developed diabetes mellitus after 1 week. After 8 weeks, myocardial functions were assessed by measuring left ventricular developed pressure (LVDP), rate of left ventricular pressure development (dp/dt max ), rate of left ventricular pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…The main pharmacological tools used to study the ACE2/ ANG-(1-7)/MAS axis are shown in FIGURE 3. Many are MAS agonists that stimulate NO production/release [ANG- (1)(2)(3)(4)(5)(6)(7), AVE 0991, CGEN 861, CGEN 856, CGEN 856S, cyclic ANG-(1-7)] (3,147,163,281,424,449,489,490,509,545,594), NorLeu3-A(1-7) (2,448). There are also two antagonists [D-Ala 7 -ANG-(1-7) (A-779) and D-Pro 7 -ANG-(1-7)].…”
Section: Pharmacological Toolsmentioning
confidence: 99%
“…The main pharmacological tools used to study the ACE2/ ANG-(1-7)/MAS axis are shown in FIGURE 3. Many are MAS agonists that stimulate NO production/release [ANG- (1)(2)(3)(4)(5)(6)(7), AVE 0991, CGEN 861, CGEN 856, CGEN 856S, cyclic ANG-(1-7)] (3,147,163,281,424,449,489,490,509,545,594), NorLeu3-A(1-7) (2,448). There are also two antagonists [D-Ala 7 -ANG-(1-7) (A-779) and D-Pro 7 -ANG-(1-7)].…”
Section: Pharmacological Toolsmentioning
confidence: 99%
“…30 The beneficial effects of AVE 0991 were confirmed in various experimental models of CVD and diabetes ( Table 1). [31][32][33][34][35][36][37][38][39][40] Despite the promising results of experimental studies, the development of AVE 0991 has been stopped for unknown strategic reasons.…”
Section: Non-peptide Ang-(1-7) Analogsmentioning
confidence: 99%
“…The two small-molecule ACE2 activators, xanthenone (XNT) and DIZE 16 increased ACE2 activity and significantly decreased blood pressure in animal models 17 and correct dysfunctional vascular repair mechanisms seen in CD34+ cells isolated from diabetic individuals 16 . Non-peptide Mas-receptor agonists are also under investigation to determine if activation of Ang(1-7)-Mas pathways produce cardio-renal protective effects in experimental models of diabetes 18 . Despite the strong mechanistic rationale for ACE2 renal protection based on animal models, very little is currently known about this emerging class in humans.…”
Section: Renal Protective Therapies Targeting Neurohormonal Activationmentioning
confidence: 99%